Optimalkan Pengelolaan Persediaan Untuk Mengurangi Kerugian: Strategi Menghadapi Permasalahan Persediaan Rusak - Hilalia, Nurul; Jumriani (Ikatan Da'i Indonesia, 2024)
Effective inventory management plays a key role in a company's smooth operations, avoiding financial losses, and maintaining its reputation. This article discusses strategies for dealing with damaged inventory problems, including identification of causes, implementation of information systems, efficient transportation plans, employee training, regular audits, return policies, and supplier diversification. This solution helps reduce the risk of damaged inventory, improves operational efficiency and strengthens the company's position in the market. The case study at CV JTS Store illustrates the application of observation and library research methods during a 4 month internship. The results show the importance of preventive measures and risk management strategies in maintaining business sustainability. Technology implementation, employee training, regular audits, and supplier diversification were identified as key steps to improve overall inventory management.